Clinical, social and psychosocial factors associated with self-rated oral health in Brazilian adolescents - Pattussi MP, Olinto MTA, Hardy R, Sheiham A. (Blackwell Synergy, 2007)
The objective of this study is to investigate the main social, psychosocial and clinical factors associated with poor self-rated oral health in adolescents.